YOUNG FARMER MOVEMENT OF MUHAMMADIYAH SIDOARJO BY HYDROPONIC URBAN FARMING - Miftakhurrohmat, A.; Abror, M.; Prihatiningrum, Andriani Eko (Journal of Social Comunity Services, 2024)
Young Farmer Movement of Muhammadiyah is under The head of the Muhammadiyah student association is in the Candi sub-district area of Sidoarjo regency which is a densely populated area and agricultural land turned into buildings and buildings. Agricultural activities must run even though environmental conditions are less supportive. The Muhammadiyah Student Association must start knowing, knowing, practicing and ready to become a cadre of young farmers because as a young cadre of Muhammadiyah at the forefront of the Muhammadiyah organization. The purpose of dedication is to introduce and practice hydroponic urban farming to harvest, post-harvest and product marketing. The basic problems for partners are: Lack of knowledge about the use of narrow land for hydroponic cultivation, manufacturing Nutrition and product marketing. The implementation methods used include counseling, training and practice as well as facilitation of supporting materials. Cultivation technology applied in yard utilization, namely hydroponics, making AB MIX nutrients and product marketing. The implementation of this service was attended by 25 teenagers who joined the Young Farmers of Muhammadiyah under the auspices of IPM Sidoarjo Candi.